2019
DOI: 10.1111/tme.12593
|View full text |Cite
|
Sign up to set email alerts
|

Staffing in hospital transfusion laboratories: UKTLC surveys show cause for concern

Abstract: Objectives:To monitor minimum standards in hospital transfusion laboratories in relation to qualifications, training, competency and the use of information technology over time against published recommendations. Background: The United Kingdom Transfusion LaboratoryCollaborative was formed in 2006 with representatives from relevant organisations and has published standards for transfusion laboratory practice. The standards are set to ensure safe transfusion laboratory practice. Regular surveys are performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…A 2014 review estimated that 53% of transfusion service/blood bank labs reported being understaffed (Chaffe et al ., ). High turnover of lab technical staff and lack of specialty‐trained/‐qualified technicians are becoming increasingly identified as major challenges to maintaining laboratory quality and minimising lab testing errors (Bolton‐Maggs et al ., ; Novis et al ., ). As fewer technical staff are being expected to perform increasing volumes of testing, any and all efforts to reduce unnecessary testing volume can be expected to have a positive impact on lab quality, as well as workplace/job satisfaction among technical staff.…”
Section: Discussionmentioning
confidence: 98%
“…A 2014 review estimated that 53% of transfusion service/blood bank labs reported being understaffed (Chaffe et al ., ). High turnover of lab technical staff and lack of specialty‐trained/‐qualified technicians are becoming increasingly identified as major challenges to maintaining laboratory quality and minimising lab testing errors (Bolton‐Maggs et al ., ; Novis et al ., ). As fewer technical staff are being expected to perform increasing volumes of testing, any and all efforts to reduce unnecessary testing volume can be expected to have a positive impact on lab quality, as well as workplace/job satisfaction among technical staff.…”
Section: Discussionmentioning
confidence: 98%
“…UKTLC standards have been considered by many laboratories during ongoing changes, especially in relation to staffing levels. However, staffing shortages have still not been addressed (Bolton‐Maggs et al, ). This, together with increased workload, contributes to lower morale and reduced job satisfaction, with many leaving for posts in other organisations or taking early retirement.…”
Section: Discussionmentioning
confidence: 99%
“…Bolton-Maggs highlighted concerns around staffing in hospital transfusion laboratories. 7 Haemovigilance has steadily improved patient outcomes after transfusion, and Wood reviewed international efforts to encourage and establish these schemes across the world. 8 Specific risks, such as vasovagal reactions and haemolytic reactions from minor mismatched platelet transfusions, were highlighted by Thijsen 9 and Swain.…”
Section: And New Interventions Andmentioning
confidence: 99%
“…Ali Pourfathollah and co‐workers described the associations of particular HLA allotypes with priming of particular blood group‐specific alloantibodies. Turning to practical matters, Burns examined the cost of transfusion, which is crucial for the planning and costing of both current services and new interventions, and Bolton‐Maggs highlighted concerns around staffing in hospital transfusion laboratories …”
mentioning
confidence: 99%